Association of Exercise Therapy and Reduction of Pain Sensitivity in Patients With Knee Osteoarthritis: A Randomized Controlled Trial1. Issue 12 (December 2014) - Henriksen, Marius; Klokker, Louise; Graven‐Nielsen, Thomas; Bartholdy, Cecilie; Schjødt Jørgensen, Tanja; Bandak, Elisabeth; Danneskiold‐Samsøe, Bente; Christensen, Robin; Bliddal, Henning
<x xml:space="preserve">Abstract</x> Objective Exercise has beneficial effects on pain in knee osteoarthritis (OA), yet the underlying mechanisms are unclear. The purpose of this study was to investigate the effects of exercise on pressure–pain sensitivity in patients with knee OA. Methods In a randomized controlled trial, participants were assigned to 12 weeks of supervised exercise therapy (ET; 36 sessions) or a no attention control group (CG). Pressure–pain sensitivity was assessed by cuff pressure algometry on the calf of the most symptomatic leg. The coprimary outcomes were pressure–pain thresholds (PPTs) and cumulated visual analog scale pain scores during constant pressure for 6 minutes at 125% of the PPT as a measure of temporal summation (TS) of pressure–pain. Secondary outcomes included self‐reported pain using the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire. Analyses were based on the "per‐protocol" population (participants following the protocol). Results Sixty participants were randomized (31 in ET group, 29 in CG), and the per‐protocol population included 48 participants (25 in ET group, 23 in CG). At followup, mean group differences in the change from baseline were 3.1 kPa (95% confidence interval [95% CI] 0.2, 6.0; P = 0.038) for the PPT, 2, 608 mm × seconds (95% CI 458, 4, 758; P = 0.019) for TS, and 6.8 points (95% CI 1.2, 12.4; P = 0.018) for KOOS pain, all in favor of ET. Conclusion Pressure–pain sensitivity, TS, and self‐reported pain are reduced among patients completing a 12‐week supervised exercise program compared to a no attention CG. These results demonstrate beneficial effects of exercise on basic pain mechanisms and further exploration may provide a basis for optimized treatment.